Chapter Poesia e filosofia a Firenze tra Santa Croce e Santa Maria Novella - GENTILI, Sonia (Reti Medievali E-Book, 2020)
This article draws a comparison between the thirteenth- and fourteenth-century library collection of the Dominican convent of Santa Maria Novella and that of the Franciscan convent of Santa Croce. Such an investigation casts new light on the links between philosophy and po- etry which enliven Dante's literary production. In particular, the author considers Aristotelian works as potential vehicles of literary knowledge about, for instance, Homeric characters.